Minimal Clinically Important Difference in Parkinson’s Disease as Assessed in Pivotal Trials of Pramipexole Extended Release - Robert A. Hauser; Mark Forrest Gordon; Yoshikuni Mizuno; Werner Poewe; Paolo Barone; Anthony H. Schapira; Olivier Rascol; Catherine Debieuvre; Mandy Fräßdorf (Parkinson's Disease)
Background. The minimal clinically important difference (MCID) is the smallest change in an outcome measure that is meaningful for patients. Objectives. To calculate the MCID for Unified Parkinson’s Disease Rating Scale (UPDRS) scores in early Parkinson’s disease (EPD) and for UPDRS scores and “OFF” time in advanced Parkinson’s disease (APD). Methods. We analyzed data from two pivotal, double-blind, parallel-group trials of pramipexole ER that included pramipexole immediate release (IR) as an active comparator. We calculated MCID as the mean change in subjects who received active treatment and rated themselves “a little better” on patient global impression of improvement (PGI-I) minus the mean change in subjects who received placebo and rated themselves unchanged. Results. MCIDs in EPD (pramipexole ER, pramipexole IR) for UPDRS II were −1.8 and −2.0, for UPDRS III −6.2 and −6.1, and for UPDRS II + III −8.0 and −8.1. MCIDs in APD for UPDRS II were −1.8 and −2.3, for UPDRS III −5.2 and −6.5, and for UPDRS II + III −7.1 and −8.8. MCID for “OFF” time (pramipexole ER, pramipexole IR) was −1.0 and −1.3 hours. Conclusions. A range of MCIDs is emerging in the PD literature that provides the basis for power calculations and interpretation of clinical trials.